EFL STUDENTS’ PERCEPTIONS TOWARDS YOUTUBE AS A LANGUAGE LEARNING RESOURCE TO IMPROVE LISTENING SKILLS: OUT OF THE CLASS CONTEXT - Sri Ratna Meldayana; Maulina Maulina; Rahmat Nasrullah (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This study investigates EFL students' perceptions of using YouTube as a language learning resource to improve their English listening skills outside the classroom. Using a qualitative research design, data were collected through open-ended questionnaires and semi-structured interviews with ten of the fourth-semester students. The data was analyzed using thematic analysis. Four main themes emerged from the data: motivation, efficacy, relevance, and attractiveness. Students viewed YouTube as an interestinglistening learning resource that offers a variety of real, flexible, and authentic content that is appropriate for self-directed learning. Because of its user-centered features and inspiring content providers, the platform was determined to be relevant to each student's unique needs, helpful in improving pronunciation and listening comprehension, and encouraging. This study highlights the value of YouTube as an informal yet impactful tool for improving English listening skills. It suggests its integration into language learning practices to support autonomous and interest-driven learning beyond the classroom.